Nivel de satisfacción estudiantil de la Unidad de Matriculación, Movilidad y Graduación en una Universidad Ecuatoriana - Cevallos Vásquez, Angie Johanna; Echeverría León, Bárbara Paulette; Sotomayor Preciado, Anita Maggie; Zhunio Bermeo, Fanny Isabel (My University, 2021)
The evaluation of university quality is a continuous process that seeks excellence of tangible and intangibleelements, in relation to whether in quantity and quality these resources are adequate for the satisfaction of the dailyactivities of the institution.Objective:To evaluate the satisfaction of the quality of the services provided by the Enrollment,Mobility and Graduation Unit (UMMOG) in the Faculty of Chemical and Health Sciences of the Technical Universityof Machala.Materials and Methods:Quantitative, descriptive and cross-sectional study. The population consistedof students belonging to the Faculty of Chemical and Health Sciences. The sample was selected through probabilisticconvenience sampling, giving a total of 281 students surveyed. Data collection was through a survey conducted by theauthors and validated by expert criteria. For data analysis, frequency and percentage tables were used for demographicvariables and the level of satisfaction using the SPSS software version 15.Results:It was determined that 60.5% of thestudents surveyed rated the attention provided by the UMMOG as fair. 51.6% of the participants do not consider theinfrastructure of the department to be adequate. Regarding enrollment, 40.57% of the student sample mentioned that thisprocess is regular.Conclusion:Most of the students rate the attention of the Enrollment, Mobility and Graduation Unitas regular and bad, that is, there is a low level of satisfaction in this aspect; and among the factors that influence thequality of the attention and services provided by the UMMOG are the treatment offered by the staff, attention schedules,time taken to resolve requests, enrollment process and infrastructure.
Introducción:La evaluación de la calidad universitaria es un proceso continuo que busca la excelencia de los elementostangibles e intangibles, en relación a si en cantidad y calidad estos recursos son adecuados para la satisfacción de lasactividades cotidianas de la institución.Objetivo:Evaluar la satisfacción de la calidad de los servicios brindados por laUnidad de Matriculación, Movilidad y Graduación (UMMOG) en la Facultad de Ciencias Químicas y de la Salud, de laUniversidad Técnica de Machala.Materiales y Métodos:Estudio cuantitativo, descriptivo y transversal. La población deestudio estuvo conformada por estudiantes que pertenecen a la Facultad de Ciencias Químicas y de la Salud. La muestra fueseleccionada a través de un muestreo probabilístico obteniendo un total de 281 estudiantes encuestados. La recopilaciónde datos fue a través de una encuesta realizada por los autores y validada a criterio de expertos, para el análisis de los datosse utilizó tablas de frecuencia y porcentaje de las variables demográficas y del nivel de satisfacción mediante el programaSPSS versión 15.Resultados:Se determinó que el 60,5 % de los estudiantes encuestados califican de regular la atenciónbrindada por la UMMOG. El 51,6 % de los participantes no consideran adecuada la infraestructura del departamento.Respecto a la matriculación el 40,57 % de la muestra estudiantil mencionan que dicho proceso es regular.Conclusión:Lamayoría de los estudiantes califica la atención de la Unidad de Matriculación, Movilidad y Graduación como regular ymala, es decir, existe un bajo nivel de satisfacción en cuanto a este aspecto; y entre los factores que influyen en la calidadde la atención y servicios que brinda la UMMOG son el trato que ofrece el personal, horarios de atención, tiempo en quedemoran en dar resolución a peticiones, proceso de matrícula e infraestructura
Keywords: CALIDAD; ESTUDIANTES; SATISFACCION; MATRICULA